COMMUNITY - DRIVEN BATIK MOTIF INNOVATION: A CASE STUDY OF SKILL DEVELOPMENT AND ECONOMIC EMPOWERMENT FOR PEOPLE WITH DISABILITIES IN MERBOK - Yusoff, Zaidi; Abdul Rahman, Azlan (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
This case study explores the implementation of a batik motif development initiative at Pusat Pemulihan Dalam Komuniti (PPDK) Merbok, focusing on empowering persons with disabilities (PWDs) through creative engagement in traditional batik design. Conducted under the University Social Responsibility (USR) and Knowledge Transfer Program (KTP), the project aimed to address the lack of unique identity in Batik Chempaka products by enabling Person with Disability trainees to design their own motifs. Before the project, participants relied heavily on existing designs, limiting product differentiation and market competitiveness. Through structured workshops and collaboration with batik experts, four original motifs were developed and transformed into wooden blocks for commercial use. The outcomes showed significant improvements in creative skills, product value, and social acceptance of batik made by people with disabilities. This initiative highlights how community-based knowledge transfer programs can drive inclusive economic opportunities through cultural entrepreneurship.